2017
DOI: 10.5551/jat.35204
|View full text |Cite
|
Sign up to set email alerts
|

Beta-adrenoceptor Activation by Norepinephrine Enhances Lipopolysaccharide-induced Matrix Metalloproteinase-9 Expression Through the ERK/JNK-c-Fos Pathway in Human THP-1 Cells

Abstract: Aim: Atherosclerosis is a chronic inflammatory disease, which leads to thrombosis and acute coronary syndrome. Matrix metalloproteinase-9 (MMP-9) is involved in the stability of the extracellular matrix (ECM) and atherosclerosis plaque. Until now, it is established that lipopolysaccharide (LPS) and norepinephrine (NE) are associated with the pathological process of atherosclerosis. However, the combined effect of LPS and NE on MMP-9 is unclear. We investigated the combined effect of LPS and NE on MMP-9 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…We found that TIMP-1 values were significantly higher in the septic patients treated with vasopressors/inotropes. Clinical studies on this topic are lacking, but experimental models imply that catecholamines have a very complex interaction with MMPs and their inhibitors [ 37 , 38 ] that could be influenced by various medications, none of which are accounted for in this research.…”
Section: Discussionmentioning
confidence: 99%
“…We found that TIMP-1 values were significantly higher in the septic patients treated with vasopressors/inotropes. Clinical studies on this topic are lacking, but experimental models imply that catecholamines have a very complex interaction with MMPs and their inhibitors [ 37 , 38 ] that could be influenced by various medications, none of which are accounted for in this research.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, irisin significantly reduced the severity of aortic atherosclerosis by blocking the activation of p-p38 MAPK in ApoE −/− mice fed on a high-cholesterol diet ( 27 ). In addition, in vitro experiments indicated that norepinephrine enhanced lipopolysaccharide-induced MMP-9 expression as well as MMP-9 activity in human THP-1 cells by promoting the activation of p-JNK ( 28 ). Furthermore, BBR protected against lipopolysaccharide-induced apoptosis by suppressing JNK-mediated signaling ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phloroglucinol administration in platelets is helpful to cardiovascular health by modulating Cox-2 activity through repressing ERK/p38 signaling [ 44 ]. In THP-1 cells, norepinephrine (NE) can induce the secretion of matrix metalloproteinase-9 (MMP-9) and augmented the progression of AS through promoting ERK/JNK-c-Fos pathway [ 45 ]. Plentiful evidence has also indicated that MAPKs and PI3K-Akt signal pathway can activate the downstream NF- κ B and enhance the progression of atherosclerosis [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%